1167 Does Maternal Intrapartum Antibiotics Prolong the Incubation Time Required for Blood Cultures to Become Positive for Infants with Early-Onset Sepsis?. (October 2012) - Sarkar, S; Sarkar, SS; Bhagat, I; Bhatt-Mehta, V
Abstract : We hypothesize that maternal intrapartum antibiotic treatment delays the growth of organism in the blood culture obtained during the workup for infants with suspected early-onset sepsis (EOS). The aim is to determine if maternal intrapartum antibiotic treatment prolongs the time to blood culture positivity in infants with EOS. Methods: Single center, retrospective review of infants with blood culture-proven EOS over a 12 years period. EOS was defined by isolation of a pathogen from blood culture drawn within 72 hours of birth and antibiotic treatment for ≥5 days. The automated bacteremia detection was with BacTAlert Peds bottles. Results: Among 88 infants with positive blood culture; 38 were deemed to have EOS, and 50 were deemed contaminants. Seventeen with EOS did not receive intrapartum antibiotics and had blood cultures drawn for being symptomatic after birth. The other 21 infants received intrapartum antibiotics and had EOS workup primarily for maternal chorioamnionitis. The median (IQR) time to blood culture positivity in all 38 infants with EOS was 19.7 h (16.5 h, 22.5 h), and the organisms grown were: Escherichia Coli in 17, Group B Streptococcus in 10, Alpha hemolytic Streptococci in 6, and other organisms in 5. The median (IQR) incubation time to blood culture positivity was not different in infants who received intrapartum antibiotics compared to infants who did not (19.6 h, IQR 16 h-28 h, versus 19.5 h, IQR 17.2 h-21.6 h, p=0.7489). Conclusion: Maternal intrapartum antiobiotic treatment did not delay the time to blood culture positivity in infants with EOS.